Strategi Komunikasi Humas Pemerintah Daerah dalam Mensosialisasikan Program Pencegahan Stunting: Studi Kasus Pada Dinas Pengendalian Penduduk dan Keluarga Berencana Kabupaten Bekasi - Hasbi Fauzi Rahman (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
A process of communication can be considered successful when komunikan receive and understand the message as defined by a communicator.It will produce an effective communication to achieve the purpose of communication.The district government bekasi are elements of government at the regional level district that has duties and functions and tasks based autonomy seluas-luasnya embedded with the autonomy in the system and the unitary state of the republic of indonesia as referred to in the country undang-undang.Who have clearly administrative matters and has the potential to improve the welfare of the citizens in accordance with their condition, features and potential of the seed of the region.In preventing stunting, of course required of local government public relations to familiarize the program so that the whole society get comprehensive information.Researchers in this wants to know how the communications strategy undertaken by Dinas Pengendalian Penduduk dan Keluarga Berencana (DPPKB)